Study Habit Predicts Examination Behaviour: An Imperative For Enhancing Quality of College Guidance and Counselling - Ossai, Moses Chukwugi (Mediterranean Journal of Social Sciences, 2011)
Study habit was investigated as a predictor of students’ examination behaviour. The sample consisted of 1290 firstyear students in tertiary institutions in Delta State. Multiple Regression was used to analyze data collected with a study habitsand examination behaviour questionnaire. It was found that study habit was a significant predictor of examination behaviour andthat gender did not significantly moderate the prediction of examination behaviour by study habits. Therefore, it wasrecommended that educational practitioners especially counselors should use measures of students’ study habits as indicatorsof their disposition towards engaging in examination malpractices thereby administering proactive counselling on them beforethey sit for examinations. This could enhance the quality of college counselling in African schools because the level ofexamination malpractices may be drastically reduced.